Meningkatkan Kemampuan Mengenal Angka 1-10 Melalui Media Benda Alam Pada Anak Kelompok A TK LPM Goin Halmahera Barat - Meiske Ester Tumbel (Peneliti.net, 2021)
This study aims to improve the ability to recognizenumbers 1-10 through the media of natural objects in group A children of TK LPM Goin west Halmahera. The beckground of this research problem is the lack of untilization of natural objects for counting and number recognition activities. This type of research is classroom action research ( CAR), taking the background of Tk Lpm Goin West Halmahera Barat. Data collection is done by observation and documentation. The data obtained were analized by reducing the data, and displaying the data. The results showed: increasing the ability to recognize numbers 1-10 through the media of natural objects in group A children of TK LPM West Halmahera. Student learning outcomes have increased from cycle I and cycle II. By using natural obects media, children’s learning outcomes increase and are included in the good category. This is also indicated by an increase in each cycle is 50%, the second cycle is 90%.